Desenvolvimento e caracterização de insertes oculares multidroga com potencial ação antiglaucomatosa. - Liege Aparecida Mapa (2023)
Glaucoma is one of the leading causes of blindness in the world. Eye drops containing drugs such as prostaglandin analogues (bimatoprost) and beta-adrenergic blockers (timolol maleate) are used in the treatment of this disease. Low adherence to treatment and limitations of the pharmaceutical form can cause lack of disease control and side effects. In this sense, new devices for drug release into the ocular cavity have been developed by our research group and described in the literature. On the other hand, treatment using more than one drug has been used in the treatment of the disease in order to synergistically increase the action of these substances. Therefore, this work aimed to develop and characterize a polymeric system in the form of inserts containing two drugs: bimatoprost and timolol maleate, for the potential treatment of glaucoma. The inserts, obtained by solvent evaporation, were developed with one, two and three layers. Physical-chemical characterizations were carried out to determine weight, determination of the content and uniformity of drug content in the inserts and in vitro release capacity of actives, thermal analyses, infrared spectrometry and Scanning Electron Microscopy (SEM). The hydration potential, surface pH were determined, in addition to the development and validation of an analytical method for the quantification of drugs. The method was developed using high-performance liquid chromatography and proved to be selective, linear, precise and accurate for the quantification of bimatoprost and timolol maleate drugs. The devices presented uniformity of weight and content in accordance with the recommendations of the main pharmacopoeias. The inserts remained intact during the hydration test with a lower water influx in those containing the drug due to possible intermolecular interactions between the drugs and the polymer. It was not possible to observe differences between the inserts with and without drugs in the infrared spectra. DSC curves did not demonstrate any thermal event related to drug degradation. These data allow inferring that there were no incompatibilities between the drugs and the polymer. The inserts presented a homogeneous and smooth surface, in addition to the identification of the different layers when analyzed by SEM. The surface pH of all inserts was 5.0 compatible with ocular use. The in vitro release test showed that the inserts had a drug release of 100%. In all inserts, under the conditions of the test carried out, release was observed for four days, with one layer releasing faster than the others. All data obtained allow inferring that the developed inserts have potential for use in the treatment of glaucoma. In vivo tests must be performed to confirm the results obtained in vitro in this work to determine the in vitro/in vivo correlation.